Metode Dakwah Yusuf Ismail Alhadid di GunungKidul - Fahmi Rusydi; Lutfiana Lutfiana (STID DI AL-HIKMAH, 2016)
The purpose of this study was to determine the method of dakwah Yusuf Ismail Alhadid conducted in Gunungkidul. This research is a descriptive qualitative research. Methods of data collection are interview, documentation and observas. Conclusion of the study is, Yusuf Ismail Alhadid proselytizing to non-Muslims in a way bilhikmah and promote morality that has exemplified the Prophet. Yusuf Islamil Alhadid also use methods mau'idzoh hasanah with advice that touches the heart and mujadalah to serve any inquiries, consultations and responses of Christians against Islam.